Square root equation

Algebra Level 4

x , y , z x, y, z are real numbers such that x 1 + 43 = y y 1 + 43 = z z 1 + 43 = x . \begin{aligned} \sqrt{x-1}+43&=y \\ \sqrt{y-1}+43&=z \\ \sqrt{z-1}+43&=x. \end{aligned} Find the sum of all possible values of x x .


The answer is 50.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chan Tin Ping
Feb 23, 2018

We can prove that x = y = z x=y=z , I put the proof below. x 1 + 43 = x x 1 + 42 = x 1 a = x 1 a + 42 = a 2 ( a 7 ) ( a + 6 ) = 0 a = 7 x 1 = 7 x = 50 \begin{aligned} \sqrt{x-1}+43&=x \\ \sqrt{x-1}+42&=x-1 \\ a=\sqrt{x-1} \\ a+42&=a^2 \\ (a-7)(a+6)&=0 \\ a&=7 \\ \sqrt{x-1}&=7 \\ x&=\large 50 \end{aligned}


Lemma: for strictly increasing function f ( x ) , h ( x ) f(x),h(x) . If f ( a ) = h ( b ) ( 1 ) f ( b ) = h ( c ) ( 2 ) f ( c ) = h ( a ) ( 3 ) \begin{aligned} f(a)&=h(b) \quad\quad(1) \\ f(b)&=h(c) \quad\quad(2) \\ f(c)&=h(a) \quad\quad(3) \end{aligned} Then a = b = c a=b=c .

P r o o f : Proof: Case1: a , b , c a,b,c are distinct numbers. Let a > b > c a>b>c . By eqn ( 2 ) (2) minus eqn ( 3 ) (3) , we got f ( b ) f ( c ) = h ( c ) h ( a ) f(b)-f(c)=h(c)-h(a) . As a > b > c a>b>c , we have f ( b ) > f ( c ) f(b)>f(c) , and h ( c ) < h ( a ) h(c)<h(a) . Hence, L H S LHS of equation above is positive. However, the R H S RHS is negative, which is contradiction. For a > c > b , b > a > c , a>c>b, b>a>c, … we can prove it similarly.

Case 2: two of a , b , c a,b,c are same, the other is distinct from them. Without loss of generality, let a = b c a=b\neq c . We get f ( a ) = f ( b ) f ( c ) , h ( a ) = h ( b ) h ( c ) f(a)=f(b)\neq f(c),h(a)=h(b)\neq h(c) . From eqn ( 2 ) (2) , f ( b ) = h ( c ) f ( a ) = h ( c ) f(b)=h(c)\\ f(a)=h(c) Substitute ( 1 ) (1) inside,we get h ( b ) = h ( c ) h(b)=h(c) , which is contradiction.

Hence, the lemma is true. Now it is obvious that f ( a ) = a 1 + 43 , h ( a ) = a f(a)=\sqrt{a-1}+43, h(a)=a are both strictly increasing function. Hence, a = b = c a=b=c .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...